Corrosion Behaviour of Tin in Stagnant Salt Solutions - El-Khouly, A.A. (Asian Journal of Chemistry, 2010)
The corrosion behaviour of tin in stagnant solutions of Cl–, SO42–, S2–, HPO42–, CO32–, NO3–,I–, SO32–, NO2–, C6H5COO–, CrO42– and vanadate ions has been studied individually. This type of study has been achieved by using potential-time, weight-loss measurements and polarization technique as well. The results obtained indicate that the corrosion behaviour of tin depends on the nature and the concentration of the anion used, and the whole process is mainly under anodic control.